Punaarmee internatsionaalsed väeosad Vene kodusõjas (1917–1922) [International troops of the Red Army in the Russian Civil War (1917–1922)] - Kopõtin, Igor (Eesti Sõjaajaloo Aastaraamat / Estonian Yearbook of Military History, 2016)
The article describes the birth of the international units of the Red Army, and their fighting activity on the fronts of the Russian Civil War. The international units were mainly made up of the prisoners of war from the Austrian-Hungarian Army, but there were also former German and Turkish POWs and even Chinese who had ended up in Russia as labourers recruited during WWI, as well as British, French and even American soldiers who had deserted or been taken prisoner from expedition corps sent against Soviet Russia.One of the reasons for forming the international units was the belief in the imminent world revolution and the hope of using the internationalists in European battles. But the internationalists themselves were motivated to join the Red Army in the hope of reaching their homeland faster and receiving clothing and food. However, the internationalists also included confirmed Bolsheviks who later became Comintern activists and some even leaders of the Eastern Bloc countries after WWII. The international units were not dispatched against Estonia, with the exception of a Chinese unit which fought in south Estonia in 1919. However, a number of former Austrian-Hungarian war prisoners were repatriated to their homeland via Estonia after the conclusion of the Tartu Peace Treaty in 1920.